Endoscopic ultrasound classification for prediction of endoscopic submucosal dissection resectability: PREDICT classification - Matsuura, Noriko; Kato, Motohiko; Iwata, Kentaro; Miyazaki, Kurato; Masunaga, Teppei; Kubosawa, Yoko; Mizutani, Mari; Hayashi, Yukie; Takabayashi, Kaoru; Takatori, Yusaku; Nakayama, Atsushi; Okabayashi, Koji; Kawakubo, Hirofumi; Kitagawa, Yuko; Yahagi, Naohisa (Endoscopy International Open, 2024)
Background and study aims The safety of endoscopic submucosal dissection (ESD) has been reported, and the risk of lymph node metastasis is low for colorectal cancer if depth of invasion is the only non-curative factor on histological evaluation. ESD is increasingly performed even if submucosal (SM) invasion is suspected. However, reports about endoscopic findings for the criteria to predict ESD resectability remain limited. Endoscopic ultrasound (EUS) can directly visualize the tomographic image of the gastrointestinal wall and may help predict ESD resectability. Therefore, we investigated the possibility of predicting ESD resectability using EUS.Patients and methods We compared the association between EUS findings and pathological results for gastric or colorectal lesions with suspected SM invasion using white light endoscopy between June 2020 and January 2023. EUS findings were grouped based on the status of the underlying the tumor, as follows: Type I, submucosal layer was observed with reproducibility; Type II, submucosal layer not fully visible; and Type III, submucosal layer disrupted and muscularis propria (MP) layer thickened.Results Forty-one gastric cancer and 22 colorectal cancer cases were analyzed. The proportions of pathological VM0 (no tumor exposed on any vertical margin) for ESD-resected specimens were 89% and 33% for Type I and II, respectively, (P ≤ 0.01). The proportions of cancer involving MP or deeper were significantly higher for Type II/III than for Type I (41% vs 0%, P ≤ 0.01).Conclusions EUS may have an important role in predicting ESD resectability of gastric and colorectal cancers suspected of having SM invasion.
Keywords: Endoscopy Lower GI Tract; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...); Endoscopic resection (polypectomy, ESD, EMRc, ...); Endoscopic ultrasonography; Gastric cancer; Rectal cancer; Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...)